Mesoporous Silica Nanoparticles for Potential Immunotherapy of Hepatocellular Carcinoma - Wu, Han; Xu, Xin-Fei; Zhu, Jia-Qi; Wang, Ming-Da; Li, Chao; Liang, Lei; Xing, Hao; Wu, Meng-Chao; Shen, Feng; Huang, Dong-Sheng; Yang, Tian (Frontiers in Bioengineering and Biotechnology, 2021)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related death worldwide, which lacks effective inhibition of progression and metastasis in the advanced clinical stage. Mesoporous silica nanoparticles (MSNs) based cytotoxic or immunoregulatory drug-loading strategies have attracted widespread attention in the recent years. As a representative of mesoporous biomaterials, MSNs has good biological characteristics and immune activation potential, and can cooperate with adjuvants against HCC. This review summarizes the possible future development of the field from the perspective of tumor immunity, and aims to stimulate the exploration of the immune mechanism of MSNs-based therapy. Through this point of view, we hope to develop new clinical immune drugs that can be applied to HCC clinical management in the future.